Evaluation of serum vitamin D levels in diabetic children and the effect of vitamin D supplementation on glycemic control (Hba1C) in vitamin D deficient diabetic children - Shetty Srinivas, Chandana Nanjaiah; Mysore Ramaraj, Savitha (International Journal of Contemporary Pediatrics, 2022)
Background: It has been estimated that around 96,000 children under 15 years are found to develop type 1 diabetes annually all over the world. Vitamin D deficiency is more common in paediatric diabetic population and vitamin D supplementation is known to improve glycemic control in Diabetic children. The objectives of the study being, to compare serum vitamin D levels of diabetic children aged less than 18 years with non-diabetic children aged <18 years and to study the effect of oral vitamin D supplementation on glycemic control in vitamin D deficient diabetic children. Methods: Present study was a cross sectional study conducted in Cheluvamba hospital, Mysuru. 60 diabetic children and 60 healthy (control) children were enrolled for the study. Serum 25(OH)D was assessed by ELISA in both groups. HbA1c levels were assessed by HPLC among vitamin D deficient diabetic children before and after supplementation of Vitamin D. Results: In current study, study group (diabetic children) mean vitamin D levels were found to be 21.667±7.9 ng/ml which were statistically significant compared to control group that is 25.90±10.06 ng/ml (p=0.012) but there was no clinical significance. Among diabetic children the mean HbA1c before and after supplementation of vitamin D among vitamin D insufficient children was 11.78±2.22% vs. 11.73±0.141% (p=0.141) respectively and in vitamin D deficient children was 11.74±1.18% vs 11.72±1.17% (p=0.662). Conclusions: Mean serum vitamin D levels were comparable among diabetic children and control group. The mean HbA1c levels were comparable before and after supplementation of vitamin D among vitamin D deficient diabetic children thus indicating that there is no role of vitamin D in glycemic control among diabetic children.